A Rare Presentation of Sarcoidosis as a Pancreatic Head Mass. (21st February 2017) - Mony, Shruti; Patil, Pradnya D.; English, Rebekah; Das, Ananya; Culver, Daniel A.; Panchabhai, Tanmay S.
Abstract : Sarcoidosis is a multisystem granulomatous syndrome of unknown etiology with noncaseating epithelioid granulomas being the pathognomonic pathological finding. Sarcoidosis most commonly involves the lungs and involvement of the gastrointestinal (GI) tract is uncommon. Pancreatic sarcoidosis is very rare, especially when it is the presenting feature of sarcoidosis and can masquerade as pancreatic cancer. Tissue infiltration in pancreatic sarcoidosis can lead to either a diffuse nodular appearance or a mass-like lesion. We present an interesting case of a 47-year-old woman with a 10-pack-year history of smoking who presented with sharp epigastric pain, weight loss, and elevated lipase level. CT and MRI imaging showed a 4 cm × 5 cm heterogeneous pancreatic mass with a dilated pancreatic duct and peripancreatic lymphadenopathy. Endoscopic ultrasound guided FNA revealed noncaseating granulomas with no evidence of malignancy or atypical infection. CT of the chest revealed bilateral mediastinal and hilar adenopathy with calcification, without any parenchymal abnormalities, and her angiotensin-converting enzyme level was elevated at 170 U/L. The clinical picture pointed to the diagnosis of pancreatic sarcoidosis. Given the severity of gastrointestinal symptoms related to pancreatic sarcoidosis, prednisone therapy at 0.5 mg/kg/day was initiated with complete resolution of symptoms at 8 weeks.